The Impact of Low-Level Viraemia on Virological Failure—Results From a Multicenter HIV Antiretroviral Therapy Cohort Study in Yunnan, China - An, Jing; Lao, Yunfei; Tang, Songyuan; Lou, Jincheng; Li, Tianshu; Dong, Xingqi (Frontiers in Medicine, 2022)
Background HIV viral load (VL) is an important indicator to monitor treatment response in antiretroviral therapy (ART). Patients on ART may experience viral blips, with low-level elevations of VL between 50 and 999 copies/mL known as low-level viraemia (LLV), but not reaching the threshold for virological failure (≥1,000 copies/mL) defined by WHO guidelines. The objective was to investigate the long-term impact of LLV on virological failure. Methods We analyzed adults who were ART naïve at baseline. LLV was defined as having an VL of 51–999 copies/mL at least once. The subjects with LLV were grouped into three categories: 51–199, 200–399, and 400–999 copies/mL. Patients with multiple episodes of LLV were classified based on the highest VL result. The subjects with LLV were also grouped by the frequency of LLV, i.e., a single episode, two consecutive episodes, two intermittent episodes, more than two consecutive episodes, and more than two intermittent episodes. Multivariable Cox models were used to predict the association of LLV with virological failure. Results A total of 93,944 subjects were included. The median number of VL tests performed was 3. There were 21,203 LLV cases, with an overall incidence of 22.6%. Most of the LLV cases were found in subjects with LVs of 50–199 copies/mL, followed by 400–999 and 200–399 copies/mL. Most of the LLV cases experienced single episodes, and the numbers of LLV with two consecutive episodes, two intermittent episodes, more than two consecutive episodes and more than two intermittent episodes were decreased successively. The risk factors associated with virological failure include: intermediate-level (200–399 copies/mL) and high-level (400–999 copies/mL) LLV, single episodes of LLV and two or more than two consecutive episodes of LLV, which may put the subjects at a 1.28–2.26-fold higher risk for virological failure. Conclusion Strengthened immediate medical attention should be placed on patients with VL of 200–999 copies/mL. The patients having experienced LLV once should be targeted for case management and repeat VL testing within 24 weeks to determine persistent LLV and monitor virological failure.